Literature Review: Cabbage Leaf Compress Intervention on Breast Swelling in Postpartum Mothers - Purwati, Ayu Endang; Heryani, Heni; Utami Asmarani, Sri; Nadiatul Mutmainah, Nida; Dwi Vanawaty, Nadya; Aini Azhar, Iva; Tina Agustin, Neng (LPPM STIKes Muhammadiyah Ciamis, 2024)
Purpose: Identify the application of cabbage leaf compress to reduce the incidence of breast swelling in postpartum mothers. Methods: literature study of 5 scientific articles obtained through the Google Scholar database, published between 2020 and 2023. Results: All studies showed that cabbage leaf compress decreased the frequency of breast engorgement in post partum mothers. Cabbage leaf compress is a non-pharmacological solution that can be used by post partum mothers independently to reduce their breast swelling. Conclusions: Giving cabbage leaf compress is effective in reducing the incidence of breast swelling in postpartum mothers.